Biosynthetic production of curcuminoids - Rodrigues, Joana Lúcia (2015)
Curcuminoids are natural phenylpropanoids from plants that have been reported as potential cancer-fighting drugs. Nevertheless, these compounds present a poor bioavailability. Cellular uptake is low and curcuminoids are quickly metabolized once inside the cell, requiring repetitive oral doses to achieve an effective concentration for therapeutic activity [1]. Herein, we report an engineered artificial pathway for the production of curcuminoids in Escherichia coli. Arabidopsis thaliana 4-coumaroyl-CoA ligase and Curcuma longa diketide-CoA synthase (DCS) and curcumin synthase (CURS1) were used and 188 µM (70 mg/L) of curcumin was obtained from ferulic acid [2]. Bisdemethoxycurcumin and demethoxycurcumin were also produced, but in lower concentrations, by feeding p-coumaric acid or a mixture of p-coumaric acid and ferulic acid, respectively. Additionally, curcuminoids were produced from tyrosine through the caffeic acid pathway. To produce caffeic acid, tyrosine ammonia lyase from Rhodotorula glutinis and 4-coumarate 3-hydroxylase from Saccharothrix espanaensis were used [3]. Caffeoyl-CoA 3-O-methyl-transferase from Medicago sativa was used to convert caffeoyl-CoA to feruloyl-CoA. Using caffeic acid, p-coumaric acid or tyrosine as a substrate, 3.9, 0.3, and 0.2 µM of curcumin were produced, respectively. This is the first report on the use of DCS and CURS1 in vivo to produce curcuminoids. In addition, curcumin, the most studied curcuminoid for therapeutic purposes and considered in many studies as the most potent and active, was produced by feeding tyrosine using a pathway involving caffeic acid. We anticipate that by using a tyrosine overproducing strain, curcumin can be produced in E. coli without the need of adding expensive precursors to the medium, thus decreasing the production cost. Therefore, this alternative pathway represents a step forward in the heterologous production of curcumin using E. coli. Aiming at greater production titers and yields, the construction of this pathway in another model organism such as Saccharomyces cerevisiae is being considered.